Effect of acute exercise on serum growth hormone and fatty acid levels in elite male water polo players - Delic, M.; Mazic, S.; Tepcic, J.; Necic, D.; Lazovic, B.; Radovanovic, D.; Cumarac-Dumanovic, M. (Archives of biological sciences, 2014)
The aim of study was to estimate the effect of acute exercise on serum growth hormone (GH) and fatty acid (FFA) levels in elite water polo players. Twelve male water polo players (20.50 ± 2.02 years) and eleven non-athletic male subjects (20.55 ± 1.04 years) participated in this study. In order to determine GH and FFA responses to acute exercise, a treadmill-running test was performed following an incremental protocol. Pre-exercise blood samples for both athletes and non-athletes were taken at 9 AM. Post-exercise samples were taken immediately after and 30 min after the treadmill running test. Water polo players had significantly lower baseline values of serum GH concentration compared to controls, whereas serum FFA concentration was significantly higher in water polo players compared to controls (p<0.01; p<0.05, respectively). In both groups, concentration of GH was significantly higher immediately after and after the 30-min of recovery compared to baseline levels (p<0.05). In water polo players, the concentration of FFA was significantly decreased immediately after and after the 30-min of recovery compared to baseline levels (p<0.05). No significant response to maximal exercise test was observed in the control group for serum FFA concentration. Our research indicates that acute exercise resulted in a significant increase in serum GH and reduction in fatty acid levels in elite water polo players.